Unveiling the Roles of Microorganisms in Promoting Environmental Sustainability - Muhammad, Shamsudeen Muhammad; Saadu, Murtala (Darul Yasin Al Sys, 2023)
The environment is described as the situations or factors that encircle an individual organism or a collection of organisms. Environmental sustainability refers to the responsible and balanced management of natural resources and ecosystems to meet the needs of the present without compromising the ability of future generations to meet their own needs. Microorganisms play a critical and multifaceted role in promoting environmental sustainability by participating in various ecological processes and functions. This paper explores the roles of microbes in maintaining environmental sustainability. Microbes, encompassing bacteria, archaea, fungi, protists, and viruses, exhibit remarkable functional diversity across diverse habitats, allowing them to contribute to key environmental challenges. The challenges facing environmental sustainability, include climate change, biodiversity loss, resource depletion, pollution, deforestation, and lack of public awareness on environmental issues. Microbes contribute significantly to addressing these challenges through nutrient cycling, bioremediation, waste management, renewable energy production, climate change mitigation, ecosystem health maintenance, and enhancing agriculture and food security. The capabilities of microbes provide promising avenues for creating a more sustainable future. By elucidating the contributions of microbes to environmental sustainability, this paper underscores their pivotal role in shaping resilient and balanced ecosystems for present and future generations. As we strive for a more sustainable future, harnessing the potential of these tiny yet powerful creatures can significantly contribute to achieving a harmonious coexistence between humanity and the natural world. Further research is needed to investigate ways to engineer and optimize microbial processes for enhanced nutrient cycling, bioremediation, and waste management.